Adjuvant Lenvatinib for High-Risk CNLC IIb/IIIa Hepatocellular Carcinoma After Curative Hepatectomy: A Prospective Exploratory Study - Sun HC; Huang ZY; Wen T; Liu L; Zhu XD; Zhang E; Li C; Zhang X; Wang J; Fan J; Zhou J (Journal of Hepatocellular Carcinoma)
Hui-Chuan Sun,1,* Zhi-Yong Huang,2,* Tianfu Wen,3,* Lianxin Liu,4,* Xiao-Dong Zhu,1,* Erlei Zhang,2 Chuan Li,3 Xiaoyun Zhang,3 Jiabei Wang,4 Jia Fan,1 Jian Zhou1 1Department of Hepatobiliary Surgery and Liver Transplantation, Liver Cancer Institute, Zhongshan Hospital, Fudan University, Shanghai, People’s Republic of China; 2Hepatic Surgery Center, Tongji Hospital, Tongji Medical College of Tongji Medical College, Huazhong University of Science & Technology, Wuhan, People’s Republic of China; 3Department of Liver Surgery, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 4Department of Hepatobiliary Surgery, the First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jian Zhou, Department of Hepatobiliary Surgery and Liver Transplantation, Liver Cancer Institute, Zhongshan Hospital, Fudan University, 136 Yi Xue Yuan Road, Shanghai, 200032, People’s Republic of China, Email zhou.jian@zs-hospital.sh.cnObjective: The risk of hepatocellular carcinoma (HCC) recurrence following surgical resection remains high, approaching 50%-70% at 5 years, with the highest risk occurring in the first year after resection. This study aimed to evaluate the efficacy and safety of lenvatinib as adjuvant therapy for HCC.Methods: In this open-label, single-arm, prospective, multicenter Phase II clinical study, a total of 51 hCC patients with China Liver Cancer (CNLC) stage IIb/IIIa (ie tumor number ≥ 4 or vascular invasion, equivalent to BCLC B/C) who underwent R0 resection 4– 6 weeks after curative surgery were enrolled. Patients received lenvatinib for up to 12 months, at a dose of 8 mg/day for body weight < 60 kg, or 12 mg/day for ≥ 60 kg. Patients were followed up every 2 months for a median of 24.1 months.Results: The median recurrence-free survival (RFS) was 16.1 months, with a 12-month RFS rate of 60.4%, exceeding the historical rate of under 50% in similar high-risk populations. The 12-month overall survival (OS) rate was 93.6%, while median OS was not reached. Treatment-related adverse events (TRAEs) occurred in 88.0% of patients, with ≥ grade 3 TRAEs in 14.0%, including thrombocytopenia and proteinuria in 6.0% of patients each, and leukopenia, neutropenia, elevated aspartate aminotransferase, and elevated alanine aminotransferase in 2.0% of patients each. AEs leading to the interruption of lenvatinib occurred in 6.0% of patients, and dose reduction was required in 18% of patients. No deaths were observed.Conclusion: Lenvatinib may be an effective adjuvant therapy for patients with CNLC stage IIb/IIIa HCC after R0 hepatectomy. However, the findings are limited by the single-arm design and small patient cohort, necessitating larger randomized controlled trials for validation.Keywords: lenvatinib, hepatocellular carcinoma, recurrence, adjuvant therapy